Effect of Green Bonds in Financing Sustainable Agriculture in Nigeria - Atinuke O. Ayo-Balogun; Chukwudumebi Cynthia Ajao; Adetunji Moses Oluwaniyi (Emerging Markets Journal)
The concept of green bonds emerged as a way to provide investors with an opportunity to contribute to environmental projects while earning returns on their investments. The study aimed to determine how green bonds affect the funding of sustainable agriculture in Nigeria. The specific objectives were to examine the role of green bonds in financing sustainable agriculture in Nigeria and to make recommendations for how to improve the use of green bonds in agriculture sector.  The study used a purposive sampling technique to select respondents from two local governments (Yewa south and Yewa north, local governments) and the respondents included farmers, deposit banks and agri-business owners in Ogun State, Nigeria. The questionnaire (survey) was used as a research instrument and a face to face interview was also conducted. The psychometric properties were tested using Cronbach’s Alpha. The results showed that the instrument used were reliable and valid. Data were analyzed using descriptive and inferential statistics, specifically a linear regression model. The t-value for the relationship between green bonds and sustainable agriculture was 22.193, and the p-value was .000. Hence, the finding revealed that a statistically significant positive relationship between green bonds and sustainable agriculture existed. As green bonds increase, sustainable agriculture increases as well. The findings had the following implications for green bond issuers, farmers and agric-business owners: Green bond issuers should prioritize investments in sustainable agriculture projects. Farmers should receive adequate training and information on sustainable agriculture practices. Finally, policymakers should create incentives for farmers who adopt sustainable practices.